Connotative Equivalence in Translation (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2014)
The article deals with connotative equivalence in translation. It is stated that the connotations are associated with the stylistic features of the language means. It is determined that the achievement of connotative equivalence in translation equivalence may occur through the use of various techniques (transcription and transliteration, loan translation, descriptive translation, rough translation, generalization).
Keywords: connotation; connotative equivalence; style; techniques of translation